91.2k views
2 votes
The form of the partial fraction decomposition of a rational function is given below.

5x^2+3x+54/(x+3)(x^2+9)=A/x+3+Bx+C/x^2+9

Find A,B,and C

1 Answer

1 vote

Answer:


A=5, B=0,C=3

Explanation:

The partial fraction decomposition is given as:


(5x^2+3x+54)/((x+3)(x^2+9)) \equiv (A)/(x+3)+(Bx+C)/(x^2+9)

We collect LCD on the RHS to obtain;


(5x^2+3x+54)/((x+3)(x^2+9)) \equiv (A(x^2+9)+(x+3)(Bx+C))/((x+3)(x^2+9))

We expand the parenthesis in the numerator of the fraction on the RHS.


(5x^2+3x+54)/((x+3)(x^2+9)) \equiv (Ax^2+9A+Bx^2+(3B+C)x+3C)/((x+3)(x^2+9))

This implies that:


(5x^2+3x+54)/((x+3)(x^2+9)) \equiv ((A+B)x^2+(3B+C)x+3C+9A)/((x+3)(x^2+9))

This is now an identity. Since the denominators are equal, the numerators must also be equal.


5x^2+3x+54=(A+B)x^2+(3B+C)x+3C+9A

We compare coefficients of the quadratic terms to get:


A+B=5\implies B=5-A...(1)

Also the coefficients of the linear terms will give us:


3B+C=3...(2)

The constant terms also gives us;


3C+9A=54...(3)

Put equation (1) in to equations (2) and (3).


3(5-A)+C=3\implies C=3A-12...(4)


3C+9A=54...(5)

Put equation (4) into (5).


3(3A-12)+9A=54


9A-36+9A=54


9A+9A=54+36


18A=90


A=(90)/(18) =5

Do backward substitution to get:


C=3(5)-12=3


B=5-5=0


\therefore A=5, B=0,C=3

Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.